2009
DOI: 10.1002/nme.2793
|View full text |Cite
|
Sign up to set email alerts
|

On the optimum support size in meshfree methods: A variational adaptivity approach with maximum‐entropy approximants

Abstract: Rosolen, A,; Millán, D. and Arroyo, M., On the optimum support size in meshfree methods: a variational adaptivity approach with maximum entropy approximants,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 26 publications
0
67
0
Order By: Relevance
“…where the set of non-negative nodal parameters {β a = γ a /h 2 a } a=1,...,N defines the locality of the approximants [25,26]. The dimensionless parameter γ a characterizes the degree of locality of the basis function associated to the node x a , while h a represents the nodal spacing.…”
Section: The Local Maximum Entropy Approximantsmentioning
confidence: 99%
See 1 more Smart Citation
“…where the set of non-negative nodal parameters {β a = γ a /h 2 a } a=1,...,N defines the locality of the approximants [25,26]. The dimensionless parameter γ a characterizes the degree of locality of the basis function associated to the node x a , while h a represents the nodal spacing.…”
Section: The Local Maximum Entropy Approximantsmentioning
confidence: 99%
“…Thanks to this property essential boundary conditions can be easily imposed on the boundary of convex domains. In addition the support of the basis functions can be flexibly controlled [25,26] and their evaluation is fast and robust using duality methods [25]. In a recent work [27] it was shown that max-ent approximants can be blended with other convex approximants such as B-splines or NURBS basis functions in the vicinity of the boundary of the domain.…”
Section: Introductionmentioning
confidence: 99%
“…We consider here LME basis functions. See [39,40,38] for the LME formulation, properties, and the evaluation of the basis functions and their derivatives. Then, let p a (ξ) denote the LME approximants associated to the point-set Ξ κ on a domain A κ ⊂ R 2 , a subset of the convex hull of the reduced node set conv Ξ κ .…”
Section: Numerical Representation Of the Surfacesmentioning
confidence: 99%
“…Recently, nonlinear manifold learning techniques have been exploited to parametrize 2D sub-domains of a point-set surface, which are then used as parametric patches and glued together with a partition of unity [38,21]. Here, we combine this methodology with local maximum-entropy (LME) meshfree approximants [39,40,5] because of their smoothness, robustness, and relative ease of quadrature compared with other meshfree approximants.…”
Section: Introductionmentioning
confidence: 99%
“…For the quartic polynomial, q = x a − x /ρ a and ρ a = γh a is the radius of the basis function support at node a. In a recent study on max-ent meshfree methods [41], it has been shown that substantial improvements in accuracy are realized by letting the supportwidth parameters as unknowns and solving for them through the variational structure (minimizing principle) of the continuum problem.…”
Section: Maximum-entropy Basis Functionsmentioning
confidence: 99%